Why train together when racing is performed alone? drafting in long-track speed skating - van den Brandt, F. A. P.; Stoter, I. K.; Otter, R. T. A.; Elferink-Gemser, M. T. (International Journal of Sports Physiology and Performance, 2021)
Purpose: In long-track speed skating, drafting is a commonly used phenomenon in training; however, it is not allowed in time-trial races. In speed skating, limited research is available on the physical and psychological impact of drafting. The aim of this study was to determine the influence of "skating alone," "leading," or "drafting" on physical intensity (heart rate and blood lactate) and perceived intensity (perceived exertion) of speed skaters.